Menimbang Kasus Pernikahan Anak dalam Kacamata Tafsir Maqasidi: Studi Kritis Ayat-ayat Pernikahan dalam Al-Qur’an - Fazlin, Hani (SUHUF, 2023)
This paper attempts to review the concept of “marriage” contained in the Qur’an as an authoritative source in Islam. This study uses the Maqāṣidī interpretation approach as an effort to reconstruct the concept of marriage. The main material object in this study is surah al-Rūm/30: 21 regarding the general concept of marriage and several other supporting verses. After conducting an in-depth analysis through the eyes of theMaqāṣidī Tafsir, the fundamental maqāṣid aspects of the marriage verses are found; ḥifẓ al-dīn, ḥifẓ al-nafs, ḥifẓ al-aql, ḥifẓ al-māl, ḥifẓ al-nasl, and ḥifẓ al-daulah. Then based on the analysis of the maqāṣid Al-Qur’an aspect, marriage consists of elements of iṣlāḥ al-fard (individual benefit), iṣlāḥ al-mujtama’ (social benefit), and iṣlāḥ al-’ālam (universal benefit). Thus, it can be concluded that child marriage has many negative impacts (disadvantages), so this practice should be prevented and stopped. This prevention requires support from all levels of society, including the government. One of them is by reviewing the implementation of a marriage dispensation for children who have not reached the minimum age limit of 19 years.